2006
DOI: 10.1262/jrd.17076
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Time Elapsed after Human Chorionic Gonadotropin Administration and Developmental Stage in Porcine Embryos Collected from Prepubertal Gilts

Abstract: Abstract. We examined the relationship between the time elapsed after human chorionic gonadotropin (hCG) administration and developmental stage of porcine embryos after collection. Prepubertal gilts, 7 to 8 months old, were given 1500 IU equine chorionic gonadotropin (eCG) intramuscularly, followed by 500 IU hCG 72 h later. The treated gilts were inseminated artificially on Day 1 (Day 0=the day of hCG administration) and on Day 2. Embryos were collected surgically on Day 6 (140, 144, and 147 h after hCG admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…Estrus synchronization was carried out (Fujino et al . ) by intramuscular injection of 1000 IU of eCG (Peamex), followed 72 h later by 500 IU hCG (Puberogen). The IVM/IVF oocytes were transferred to NCSU‐37 supplemented with 4 mg/mL BSA and 25 mmol/L HEPES, after adjustment of the osmolarity to 280 mOsm/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrus synchronization was carried out (Fujino et al . ) by intramuscular injection of 1000 IU of eCG (Peamex), followed 72 h later by 500 IU hCG (Puberogen). The IVM/IVF oocytes were transferred to NCSU‐37 supplemented with 4 mg/mL BSA and 25 mmol/L HEPES, after adjustment of the osmolarity to 280 mOsm/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Embryo transfer (ET) and in vitro culture of IVM/IVF oocytes We used 7-8-month-old prepubertal crossbred gilts (Landrace, Large White and Duroc breeds) as recipients of IVM/IVF oocytes. Estrus synchronization was carried out (Fujino et al 2006) by intramuscular injection of 1000 IU of eCG (Peamex), followed 72 h later by 500 IU hCG (Puberogen). The IVM/ IVF oocytes were transferred to NCSU-37 supplemented with 4 mg/mL BSA and 25 mmol/L HEPES, after adjustment of the osmolarity to 280 mOsm/kg.…”
Section: Ivf Of Ivm Oocytesmentioning
confidence: 99%
“…The use of eCG, in this study, served the propose to induce superovulation, as the animals that received eCG showed a higher number of ovulations, compared to the other treatment groups, and since Brazilian Piau breed has average of 11.1±2.4 in ovulation rate, number of total pigs born (9.3±2.7) and pigs born alive (7.9±2.6) (Silva et al, 2011). Also seen in other studies with averages of more than 20 ovulations in commercial breeds, when the dosage applied was equal to or greater than 1000 IU (Besenfelder et al, 1997;Hazeleger et al, 2000;Rátky et al, 2001;Fujino et al, 2006;Kauffold et al, 2007;Sommer et al, 2007;Martinat-Botté et al, 2010). Given that eCG activity is similar to FSH and LH (Brüssow et al, 2009;Soede et al, 2011;Driancourt et al, 2013;De Rensis and Kirkwood, 2016), a dosage of 1000 IU triggers greater follicular growth, stimulating greater numbers of follicles to grow and develop LH receptors and, subsequently, to ovulate, resulting in a larger amount of CL.…”
Section: Discussionmentioning
confidence: 68%
“…In vivo-produced morulae were collected and vitrified according to the method reported by Fujino et al (2006). Briefly, 7-to 8-month-old prepubertal Landrace gilts were given an intramuscular injection of 1500 IU of eCG, followed 72 h later by 500 IU hCG to induce superovulation.…”
Section: Vitrification and Warming Of In Vivo-produced Embryosmentioning
confidence: 99%
“…Estrus synchronization was carried out by intramuscular injection of 1000 IU of eCG, followed 72 h later by 500 IU hCG (Fujino et al 2006). The in vitro-produced parthenotes and vitrified-warmed morulae were transferred to NCSU-37 supplemented with 4 mg/mL BSA and 25 mmol/L HEPES, after adjustment of the osmolarity to 280 mOsm/kg.…”
Section: Embryo Transfer (Et)mentioning
confidence: 99%